Enhanced energy storage properties in sodium bismuth titanate-based ceramics for dielectric capacitor applications. Issue 21 (14th May 2019) - Wu, Yichen; Fan, Yuzhu; Liu, Ningtao; Peng, Ping; Zhou, Mingxing; Yan, Shiguang; Cao, Fei; Dong, Xianlin; Wang, Genshui
Abstract : The strategy of turning ferroelectric into relaxor is feasible and effective to boost the energy density and efficiency for sodium bismuth titanate-based bulk ceramics. Abstract : There are imperious demands for developing eco-benign energy storage materials with high-performance in a sustainable society. In this paper, we introduce Sr0.85 Bi0.1□0.05 TiO3 (SBT) and NaNbO3 (NN) into Bi0.5 Na0.5 TiO3 (BNT) ceramics through compositional design. The introduction of Sr 2+ ions and vacancies at the A-sites constructs relaxor ferroelectrics according to order–disorder theory. The introduction of Nb 5+ ions at the B-sites is confirmed to have two major implications. In one way, it boosts a higher induced polarization due to its intrinsic larger polarizability and overall stronger degree of diffuseness. In another, it contributes to forming a core–shell microstructure, as proven using transmission electron microscopy, promoting the breakdown strength (BDS) to a higher level. With the above strategies, our BNT–SBT–4NN ceramics demonstrate excellent energy storage performances with simultaneously ultrahigh energy storage density ( W ∼ 3.78 J cm −3 ), recoverable energy storage density ( W rec ∼ 3.08 J cm −3 ) and efficiency (81.4%). Furthermore, the ceramics possess excellent discharge energy density ( W d = 0.854 J cm −3 ) and rapid discharge speed ( t 0.9 ∼ 100 ns) in a wide temperature range, proving their high application potential. Our results break through the bottleneck of BNT-based ferroelectrics with a general recoverable energy storage density of lower than 3 J cm −3, making the BNT–SBT–4NN ceramic a powerful candidate material for use in energy storage applications.